"Mas e se essa festa se acabar? Ai meu Deus o que será de mim? : as tradições do Divino Espírito Santo de Pirenópolis-GO em registros audiovisuais - (:unkn) unknown (Universidade Estadual de Goiás, 2016)
This dissertation discusses under the bias of the historiographical search the origin of the Holy Divine Spirit Festival of Pirenopolis, State of Goias, charting on their ancestry medieval roots and how they get along in current time / space from the perspective of the categories: popular culture , pastiche, Medievalism and Medieval Reminiscence. After such a historical- linear plot, it is discussed about the Media-Festival interaction and as the Cinema under a coutiniana perspective produced audiovisual material about this celebration, still dialoguing issues pertaining to representation in Chartier and spectacularization in Martin-Barbero. This route is done in order to understand four videos on the aforementioned festival afterwards, generating analysis of such media oriented in Jean-Claude Bernardet thesis that deals with those who produce media that represent a given community, which in Bernardet vision is much better to the residents be the ones who are responsible for directing such representative action. The media analyzed during the search were: a report from Globo Rural (1995), the Videofocus (1988), Iphan (2008) and the local company, Morro Alto Tourism (2007). It is yet researched is this study the forms of representation of this celebration from the personal social networks like Facebook and Instagram.exhibition of some local residents. From the theoretical and historical and analytical contribution on such media, either audiovisual, or coming from social networks it was possible to draw a form of instrumentalization of these social media as part of continuities and discontinuities processes of the Festival itself, as well as the satisfaction level verification on the representation of media produced by internal community subjects.
Keywords: Festa do Divino Espírito Santo; Festa do Divino Espírito Santo - Audiovisual; Pirenópolis; Cultura Popular; Holy Divine Spirit Festival; Holy Divine Spirit Festival - Audio-visual; Pirenópolis; Popular Culture; CIENCIAS HUMANAS::HISTORIA; CIENCIAS HUMANAS::SOCIOLOGIA; TEOLOGIA::TEOLOGIA SISTEMATICA